Managing Local Bleeding in Dentoalveolar Surgery: Practical Techniques and Best Practices: A Narrative Review - Rahmani, Fatemeh; Nikeghbal, Dorsa; Zarehgar, Sayeh; Mohammadikhah, Meysam; Aryanezhad, Seyed Sasan; Mahmoudi Anzabi, Reza; Zareanshahraki, Mehran; Goodarzi, Ali (Galen Medical Journal, 2024)
Effective management of local bleeding is essential for safe and successful dentoalveolar surgery, particularly among patients with bleeding disorders, those on anticoagulant therapy, or individuals with systemic conditions affecting hemostasis. This narrative review explores practical and advanced approaches for controlling bleeding in dentoalveolar procedures, with a focus on patient-centered strategies that minimize risk while accommodating complex clinical needs. Based on this narriative review, Beginning with an overview of the pathophysiology of bleeding in the oral cavity, the review examines conventional methods such as mechanical compression, sutures, and the use of local anesthetics with vasoconstrictors. Further, it evaluates the application of pharmacological agents, including topical hemostatic products like gelatin sponges, oxidized cellulose, and tranexamic acid, which have shown efficacy in high-risk patients without disrupting systemic anticoagulation therapy. For special populations, including those with congenital coagulopathies and liver disease, tailored approaches are reviewed to address unique bleeding challenges. Additionally, innovative hemostatic materials and laser-assisted techniques are discussed as emerging options that promise enhanced safety and effectiveness in complex cases. By synthesizing current knowledge on bleeding control methods, this review provides clinicians with practical guidance for optimizing hemostasis in dentoalveolar surgery. The insights and recommendations presented aim to improve patient outcomes, reduce perioperative complications, and support a balanced approach to local and systemic hemostatic management in diverse patient groups.